High energy Compton spectroscopy and electronic structure of Laves phase ZrFe2. (August 2016) - Bhatt, Samir; Kumar, Kishor; Arora, Gunjan; Bapna, Komal; Ahuja, B.L.
Abstract: We present the first-ever experimental Compton profile of Laves phase ZrFe2 using indigenous 20 Ci 137 Cs Compton spectrometer. To annotate the experimental electron momentum density, we have calculated the theoretical Compton profiles using density functional theory (DFT) and hybridization of Hartree–Fock and DFT within linear combination of atomic orbitals (LCAO) method. The spin-polarized energy bands and density of states are computed using LCAO and full potential-linearized augmented plane wave methods. The revised Perdew-Burke-Ernzerhof functional (for solids) based theoretical profile gives a marginally better agreement with the experimental profile as compared to other approximations considered in the present work. The Fermi surface topology of ZrFe2 is explained in terms of majority- and minority-spin energy bands. Highlights: First-ever Compton profile (CP) measurements of ZrFe2 using 137 Cs source. Analyzed CP data in terms of first-ever LCAO-DFT calculations. DFT-PBEsol based CP is found to be in better agreement with experimental CP. Analysed energy bands and DOS using PBEsol with LCAO and FP-LAPW schemes. First attempt to deduce FS topology.